LSC 2016: from system approaches in lung disease to getting the job you want. Issue 2 (June 2016) - Boots, Agnes; Flood, Emma; Kahn, Nicolas; Hardavella, Georgia; Bikov, Andras; Aamli, Ane; Skoczynski, Szymon
The Lung Science Conference (LSC) 2016 generated, as in previous years, fruitful discussions and exciting networking opportunities in the breathtaking venue of the Palace Hotel, Estoril, Portugal. Highlights of the Lung Science Conference 2016 http://ow.ly/4nsKG2